2021
DOI: 10.7575/aiac.ijels.v.9n.2p.90
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the 21st Century Skills into the Curriculum of Social Studies Course

Abstract: This study aimed to investigate the reflections of the 21st century skills into the curriculum of social studies course in Turkey. The classification made by the institutions classifying the 21st century skills in line with this objective has been examined and the classification made by the Partnership for 21st Century Skills (P21) has been considered as it has been generally accepted. The study investigated the reflections of the 21st century skills on social studies curriculum being subject to detailed conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In other words, there is that friendship and spirit of unionism and solidarity developed through collaboration. These results appear to support Erol's (2021) opinion that due to teamwork, productivity increases.…”
Section: B Learning and Innovation Skillssupporting
confidence: 81%
See 2 more Smart Citations
“…In other words, there is that friendship and spirit of unionism and solidarity developed through collaboration. These results appear to support Erol's (2021) opinion that due to teamwork, productivity increases.…”
Section: B Learning and Innovation Skillssupporting
confidence: 81%
“…It is of course important for every country to embrace such skills in order to produce global citizens. At present, there is a growing body of literature supporting the view that there is radical transformation of the education system in order to address the demands of the perpetually changing world (Erol, 2021;UNESCO, 2015;Welker & Mohr, 2017). As it had been discussed in the preceding chapter, Lesotho is not an exception to this global initiative to promote 21 st century skills.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The developers of teaching materials are encouraged to internalize themes and topics in factual and contextual teaching materials to support the intended meaningful learning paradigm. Global awareness, financial literacy, economics, business, entrepreneurship, digital literacy, citizenship, health, and environmental literacy are just a few of the themes covered in 21 st -century education that are factual, contextual, and relevant to current learning demands (Alismail & McGuire, 2015;Erol, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With the outbreak of the global Covid-19 pandemic (Hossain et al, 2020), which imposed unparalleled challenges on traditional or direct education, many educators in educational institutions called for the adoption of an educational system that includes the life skills and knowledge necessary to deal with all these developments and challenges (Islam & Habib, 2021;Kar, 2011;Yildiz & Zingin, 2021).World Health Organization has identified essential life skills that enable individuals to successfully deal with the demands and difficulties of daily life which known as 21st century skills (Ananiadou & Claro, 2009;Prajapati et.al, 2017). In fact, 21st-century skills have been defined and classified differently based on the different perspectives of various institutions and organizations (Erol, 2021;Saleh et al, 2022;Yildiz & Zengin, 2021); that identified the required qualification and competencies needed for the staff under the name of 21st-century skills (Arslan-Cansever et. al., 2021;Binkley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%